Key policy actions for sustainable land and water use to serve people - Joachim von Braun; Ashok Gulati; Homi Kharas (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
To achieve food security for all, new resource policies for sustainable land and water use are needed. Land, water and energy need to be considered jointly in policies, not in isolation. United Nations, G20 countries' policy makers, corporate and civil society actors, and those of other countries should act in coordinated fashion in the following four policy areas on which specific proposals are made in this policy paper: 1) focusing land, and water resource policies on human wellbeing, 2) investing in and sharing water, agricultural and energy innovations, 3) making wider use of digital opportunities for sustainable agriculture, and 4) re-designing global governance of agriculture and food.
Keywords: F53; Q10; Q18; Q28; 330; G-20; international resource policy; sustainable agriculture; food security